Unmasking trends and drivers of the international arachnid trade - Herzig, Volker; Hauke, Tobias J.; Lüddecke, Tim (Frontiers in Arachnid Science, 2023)
The global biodiversity crisis represents a major threat to humanity with the worldwide animal trade being identified as a major driving force. While vertebrate trade has been subject to intensified research, the extent of invertebrate trade remains understudied. Recent analyses for arachnids (i.e. spiders and scorpions) suggested a large and still expanding international market with potential to threaten natural populations. Whether captive breeding has the potential to decrease collection pressure on wild arachnid populations has not been investigated nor were the temporal dynamics or the trade purposes of arachnids been examined. We herein seek to broaden our understanding of these areas by analysing tarantula and scorpion import and export data from two major international wildlife trade databases (CITES and LEMIS). Historically a large proportion of arachnids has been traded for the pet sector. According to our analysis of the LEMIS data, imports of pet arachnids have been declining by up to >55% within a decade. Furthermore, annual breakdown of US imports unveiled that at least 43% of specimen are not traded as pets but for other purposes, including research, souvenirs, and traditional medicine, with the souvenir sector experiencing an unprecedented growth. CITES data for protected tarantulas, but not scorpions, further indicate a shift towards trade with captive-bred specimen. These trends need to be considered for any efforts aiming to conserve natural populations. Coordinated captive breeding may represent a path towards increased sustainability by covering the demand for traded arachnids, while also providing an important resource for scientific research across disciplines.